Caracterização da serie Piracicaba - Dematte, J.L.I. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1970)
This paper deals with the study and classification of a proposed Piracicaba soil series. Four soil profiles were described studied and classified according to the 7th Approximation. By using a centrifugation method the clay was separated into two fractions: between 2 to 0,2 u and down to 0,2 u, respectivelly coarse and fine clay fractions. The results show a silt content variying between 9.70 ± 0.33 to 21.06 ± 0.50 % and a clay content between 27.05 ± 34.95 ± 0.88 % in the B2 horizons. The Piracicaba soil series is a Typic Tropudalf and does not fit the criteria for Red Yellow Podzolic variação Piracicaba established in 1960 by the COMISSÃO DE SOLOS.